Improving Students’ Speaking Performance Through Critical Method - Husni Tamrin; Muhammad Basri Jafar; Fatimah Hidayahni Amin (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2024)
This study investigates the impact of the critical method on improving students' speaking performance and identifies key obstacles hindering their abilities. This research employed a mixed method with convergent parallel design. The population of this research was the students of Madrasah Aliyah (MA) Madani Alauddin in the eleventh grade of science consist of 115 students, 53 male and 62 female. Quantitative data were analyzed using Heaton’s rating score for accuracy and fluency, descriptive statistics, and paired samples t-test via SPSS while qualitative data were analyzed through miles & Huberman’s’ qualitative analysis to identify patterns and themes related to the obstacles faced by students. The findings revealed a significant improvement in students' speaking scores, with the mean score increasing from 46.25 in the pre-test to 70.625 in the post-test. Key obstacles identified included nervousness, fear of making mistakes, lack of vocabulary, and lack of confidence. Despite cognitive improvements, persistent nervousness highlighted the need for additional emotional and psychological support. A major implication is the recommendation to shift from static to dynamic assessment methods, which focus on continuous evaluation and can reduce anxiety, fostering a more supportive learning environment. This study addresses a critical gap in the literature by providing empirical evidence of the effectiveness of the critical method and suggests future research directions, including the exploration of long-term impacts and the application of dynamic assessments across diverse educational contexts. The study concludes that integrating cognitive and emotional support strategies in language education can significantly enhance students' speaking performance and overall well-being.